TATA KELOLA REKAM MEDIS BERBASIS ELEKTRONIK DALAM MONITORING PASIEN HEMODIALISA DI RSUD AL-IHSAN - Febyana, Feby; Nursamsiyah, Rosa (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
This study aims to analyze the implementation of electronic-based medical record management using the waterfall method in monitoring hemodialysis patients at AL-IHSAN Hospital. The results of our research show that there are still manual hemodialysis patient services, namely dialysis scheduling services for hemodialysis patients, that have previously been scheduled by specialist doctors. What is currently being done is that management is still manual, so it requires time and accuracy to schedule when patients will be scheduled for dialysis. The research method that we use in our current scientific work is qualitative with a descriptive approach using the waterfall software design process. Then distributing questionnaires and interviews. This approach allows stakeholders to clearly understand system requirements and execute each development phase sequentially. Electronic-based medical record management results in increased efficiency in the process of monitoring hemodialysis patients, especially routine scheduling of patients who are already integrated with the system. Information that is well documented and available centrally reduces the need to search physical records or fill out forms manually. This saves medical staff time and effort, allowing them to focus on patient care.